2015
DOI: 10.3945/jn.115.210104
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Plasma Phospholipids in Men Are Influenced by the Source of Dietary Fat

Abstract: The changes in postprandial plasma phospholipids in men relate to the diet composition and the relative size of the endogenous phospholipid pools. Despite similar lipemic responses as measured by changes in triglyceride concentrations, the differential responses to dairy and soy meals derived through lipidomic analysis of phospholipids suggest differences in the metabolism of soybean oil and dairy fat. The increased concentrations of plasmalogens, with potential antioxidant capacity, in the postprandial period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 43 publications
0
48
1
Order By: Relevance
“…Several structurally different ceramides are among the lipid metabolites profiled by current metabolomics platforms. Recent evidence from two small short-term intervention studies found that ceramide concentration could be transiently decreased by adopting a healthy dietary pattern 15 and changes in primary dietary sources of fat 16 . The MedDiet might also exert its effect through decreasing ceramide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Several structurally different ceramides are among the lipid metabolites profiled by current metabolomics platforms. Recent evidence from two small short-term intervention studies found that ceramide concentration could be transiently decreased by adopting a healthy dietary pattern 15 and changes in primary dietary sources of fat 16 . The MedDiet might also exert its effect through decreasing ceramide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…GTT was assessed using a Mouse Insulin ELISA kit (ALPCO Diagnostics, Salem, New Hampshire). Lipids were extracted from ~10 μL of plasma obtained from cardiac puncture using 20 volumes of chloroform:methanol (2:1) in a single‐phase extraction process, recovering all lipids in a single phase suitable for liquid chromatography–mass spectrometry analysis, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Of interest, although PE and PC plasmalogens have been shown to be negatively associated with many diseases, such as coronary artery disease and diabetes (Meikle et al, 2011(Meikle et al, , 2013Sutter et al, 2016), our results indicate that some plasmalogen species (PE(P-18-1/22:4)(a), PE(P-16:0/22:4), and PC(P-18:1/22:6); Figure 5) are positively associated with pathological cardiac remodeling. Finally, when considering the potential of any lipids as biomarkers, it is important to note that some lipids can be altered by different diets, and this should be considered in future studies (Meikle et al, 2015).…”
Section: Opposing Changes In Individual Lipids In Physiological Versumentioning
confidence: 99%